2017
DOI: 10.1186/s12886-017-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes, spectacles dependence and patient satisfaction of multifocal and accommodative intraocular lenses: innovative perspectives for maximal refractive-oriented cataract surgery

Abstract: BackgroundThe aim of this study was to evaluate visual outcomes for different working distances (far, 60 cm and 33 cm) and impact on vision quality of multifocal IOLs AcrySof ResTOR SN6AD1 and SN6AD3 (Alcon, Inc., Fort Worth, Texas, USA) as well as REVIEW FIL611PV multifocal and OPTOFLEX FIL618 accommodative IOLs (Soleko, Ltd., Rome, Italy) in patients undergoing bilateral phacoemulsification.MethodsIn this observational prospective study 63 patients undergoing binocular cataract surgery were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
2
24
2
1
Order By: Relevance
“…16 On the other hand, these results are superior to those of previous studies with implantation of bilateral multifocal IOLs. 18,19 In addition, the rate of spectacle independence was higher in our study than in the CONCERTO study. Our findings that 93.8% of subjects reported that they would recommend mix-and-match implantation of diffractive multifocal IOLs with +2.75 D and +4.00 D add powers to their friends and relatives indicated that despite some visual problems, these symptoms did not have a significant impact on overall satisfaction.…”
Section: Discussioncontrasting
confidence: 64%
“…16 On the other hand, these results are superior to those of previous studies with implantation of bilateral multifocal IOLs. 18,19 In addition, the rate of spectacle independence was higher in our study than in the CONCERTO study. Our findings that 93.8% of subjects reported that they would recommend mix-and-match implantation of diffractive multifocal IOLs with +2.75 D and +4.00 D add powers to their friends and relatives indicated that despite some visual problems, these symptoms did not have a significant impact on overall satisfaction.…”
Section: Discussioncontrasting
confidence: 64%
“… 1 Lens replacement surgery with MIOL technology can offer patients with cataracts the opportunity to be less dependent on, or even free of, eyeglasses, readers, or bifocals after cataract surgery. 2 , 3 This flexibility provides not just a solution to eliminate glasses, but a functional convenience that allows patients with cataracts to conduct their daily living activities in an unencumbered manner.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Multifocal IOLs have also been shown to improve visual rehabilitation, in particular, in providing patient independence for different working distances as well as reducing spectacle dependence. 4,5 However, halos, glare, and reduced contrast sensitivity continue to be reported with presbyopia-correcting IOLs. 6,7 Multifocal IOLs can be broadly categorized based on their design: either concentric focal zones (alternating for near, intermediate, or far) or segmented, two zones (bifocal) with one zone for distance and the other for near.…”
mentioning
confidence: 99%